Acute oxalate nephropathy associated with orlistat - Youshay Humayun; Kenneth C. Ball; Jack R. Lewin; Anna A. Lerant; Tibor Fülöp (Society of Diabetic Nephropathy Prevention, 2016)
Background: Obesity is a major world-wide epidemic which has led to a surge of various weight loss-inducing medical or surgical treatments. Orlistat is a gastrointestinal lipase inhibitor used as an adjunct treatment of obesity and type 2 diabetes mellitus to induce clinically significant weight loss via fat malabsorption. Case Presentation:We describe a case of a 76-year-old female with past medical history of chronic kidney disease (baseline serum creatinine was 1.5-2.5 mg/dL), hypertension, gout and psoriatic arthritis, who was admitted for evaluation of elevated creatinine, peaking at 5.40 mg/dL. She was started on orlistat 120 mg three times a day six weeks earlier. Initial serologic work-up remained unremarkable. Percutaneous kidney biopsy revealed massive calcium oxalate crystal depositions with acute tubular necrosis and interstitial inflammation. Serum oxalate level returned elevated at 45 mm/l (normal <27). Timed 24-hour urine collection documented increased oxalate excretion repeatedly (54-96 mg/24 hour). After five renal dialysis sessions in eighth days she gradually regained her former baseline kidney function with creatinine around 2 mg/dL. Given coexisting proton-pump inhibitor therapy, only per os calcium-citrate provided effective intestinal oxalate chelation to control hyperoxaluria. Conclusions: Our case underscores the potential of medically induced fat malabsorption to lead to an excessive oxalate absorption and acute kidney injury (AKI), especially in subjects with pre-existing renal impairment. Further, it emphasizes the importance of kidney biopsy to facilitate early diagnosis and treatment.